Youth Obesity: Sport as a Solution Strategy - Pietrzak, Krzysztof; Wasilewska, Małgorzata; Polok, Sebastian; Demel, Karol (Quality in Sport, 2025)
Purpose: This study examines organized sports as a multisectoral intervention against youth obesity, emphasizing physiological, psychosocial, and structural motivations. Materials and Research Methods: Long term cohort analyses (e.g., Finland’s 21-year tracking [7]), randomized trials, and regional case studies (Poland’s rural-urban disparities [10], Italy’s post-pandemic park programs [15]) were included. Data spanned adiposity metrics, accelerometry, mental health outcomes, and policy evaluations. Basic Results: Sustained sports participation reduced adulthood obesity risk by 26%, mediated by metabolic improvements and visceral fat loss [6,7]. Team sports enhanced adherence (30% higher retention) through social engagement, correlating with a 40% decline in depressive symptoms [3,9]. Rural-urban gaps (20% participation disparity) and gender-based attrition (35% female dropout by age 15) highlighted systemic inequities [9,10]. Culturally tailored initiatives, such as Poland’s folk dance revival and Verona’s community sports, boosted engagement by 32–60% [9,15]. Conclusions: Effective strategies require subsidized infrastructure in poorer regions, clinical integration of sports prescriptions, and gender-inclusive attitude. Policies must connect global evidence with local traditions, repurposing spaces like abandoned factories into activity hubs [25] and setting “exercise vital signs” into pediatric care [24]. Success depends on contextual adaptability- transforming sports from occasional leisure into a part of healthy life foundation.